(3OaY GdSehes - (3GdbQWHj , ehSi Hf ejehf Hf YHjOGddg GdGSQGFjdj,J (B601 (3g` s
(3ChdgG (B:s
(3bO TgQ ai CYUGQfG haj EbdjefG gPG , aj YOI CbGdje SjQI ehdGfG GdbGVi GdLd GdaGVd Pdc Gf ehdGfG GeQ GdCWHGA HeUQ Cf jYedhG GdOQjGb GdcHjQ heYLhf eKQjOjWhS, hYed gPjf ai eOjfI eUQ YSQ LOkG s
(3BNQgG (B:s
(3hcPdc LhReGKd jbJd efg RfI eKbGd HNGUjI ajg s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B93 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMji HGTG GdLdjdj (B- (3GdehUd (B(8) s
Keywords: (3GdWHs